Effects of Nitrogen and Calcium Nutrition Withdrawal Before Harvesting on Biomass and Nutritive and Safety Quality in Spinach (Spinacia Oleracea L.) - Li, Yan; Yingpeng, Zhang; Zhaohui, Liu; Ziwen, Zhong; Ming, Sun (Journal of plant nutrition, 2014)
A hydroponic culture was used to study different nitrogen and calcium supply patterns on biomass, nutritive, and safety quality of spinach seven days before harvesting. The results showed that the complete or partial withdrawal of nitrogen (N) and calcium (Ca) nutrient decreased spinach biomass compared to control (CK). At the same time, the withdrawal of N and Ca supply before harvesting increased vitamin C contents and decreased nitrate and oxalate content in edible parts of spinach. The decrease in spinach biomass could be partially compensated by the increase of the nutritive and safety quality of spinach and the reduced use of N and Ca nutrients.